Values & ethics in social work - Beckett, Chris 1955-; Maynard, Andrew; Jordan, Peter (London SAGE Publications Ltd, 2017)
This introductory text is designed to equip students with a sound understanding of the principles of values and ethics which no social worker should be without.
pt. 1. Foundations of Values and Ethics -- 1. What are Values and Ethics? -- 2. Moral Philosophy -- 3. Values and Religion -- 4. Values and Politics -- 5. Realism as an Ethical Principle -- pt. 2. Values and Ethics in Practice -- 6. Being Professional -- 7. Uses and Abuses of Power -- 8. Risk and blame -- 9. Self-Determination and Privacy -- 10. Respect or Oppression -- 11. Limited Resources -- 12. Difference and Diversity.
Previous edition: 2013.
Includes bibliographical references (pages 163-172) and index.
Keywords: Social service -- Moral and ethical aspects; Social workers -- Professional ethics; Social values -- Study and teaching; Professional ethics -- Study and teaching